2010
DOI: 10.1063/1.3510488
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion and cyclic stretching of Au thin film on poly(dimethyl-siloxane) for stretchable electronics

Abstract: This paper presents the results of an experimental study of the effects of cyclic damage and adhesion on nanoscale Au thin films deposited on a flexible poly(dimethyl-siloxane) substrate. The deformation and cracking mechanisms are elucidated as functions of film thickness. The implications of the results are also discussed for the design of stretchable electronic structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
53
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 21 publications
4
53
0
Order By: Relevance
“…[64] As a proof of concept, we demonstrate that the stretchable electrode can be used to detect EMG signals and that the stretchable strain sensor can be utilized to simultaneously monitor the deformation induced by the elbow bending. [50][51][52][53][54][55][56][57][58][59][60][61] Adhesion is crucial for the long-term use of stretchable electronics, such as the detection of body-surface biosignals in electromyography (EMG) and electrocardiography (ECG), and implanted devices where the interface friction may easily induce failures of debonding. It also opens up for exploration of the advanced property-function relationships combining high adhesion and stretchability.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[64] As a proof of concept, we demonstrate that the stretchable electrode can be used to detect EMG signals and that the stretchable strain sensor can be utilized to simultaneously monitor the deformation induced by the elbow bending. [50][51][52][53][54][55][56][57][58][59][60][61] Adhesion is crucial for the long-term use of stretchable electronics, such as the detection of body-surface biosignals in electromyography (EMG) and electrocardiography (ECG), and implanted devices where the interface friction may easily induce failures of debonding. It also opens up for exploration of the advanced property-function relationships combining high adhesion and stretchability.…”
mentioning
confidence: 99%
“…[50][51][52][53][54][55][56][57][58][59][60][61] Adhesion is crucial for the long-term use of stretchable electronics, such as the detection of body-surface biosignals in electromyography (EMG) and electrocardiography (ECG), and implanted devices where the interface friction may easily induce failures of debonding. This is due to the huge difference in physical and chemical properties (e.g., Young's modulus: tens of GPa for gold while only several MPa for PDMS) between the conductive material and the elastic substrate.…”
mentioning
confidence: 99%
“…The film exhibited a plane‐strain modulus of ≈133 MPa which is much lower than that of a previously reported 100‐nm‐thick Au film (≈53 GPa) and a bulk Au thin film (82 GPa) . This result implies that the TB‐Au NP‐coated PDMS film can significantly lower the probability of mechanical failures, such as fracture or delamination of Au NP arrays on PDMS under external mechanical stimuli . In addition, it was observed that the stretchability of the (TB‐Au NP/TA) n ‐coated PDMS in dried state was notably decreased compared to that of bare PDMS although the (TB‐Au NP/TA) n multilayers induced the formation of wrinkled structure of PDMS substrate (Figure S11, Supporting Information).…”
mentioning
confidence: 61%
“…Generally, wrinkled elastomeric conductors have been prepared through metal deposition onto prestrained elastomers in uniaxial or biaxial direction . However, these conductors cannot maintain high electrical conductivity under mechanical strain, experiencing cracking/disconnection of the continuous metallic thin layer as well as delamination between the metallic layer and the elastomeric substrate . Additionally, prestrain and metal deposition processes pose much difficulty in preparing large‐area wrinkled elastomeric electrodes.…”
mentioning
confidence: 99%
“…International collaborations among the United States and Africa, [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] J oint US-Africa Materials Institute (JUAMI) will be held December 10-21, 2018, in Kampala, Uganda. JUAMI features tutorials on cutting-edge energy materials topics, hands-on experiments and learning activities, and research seminars.…”
Section: In Summarymentioning
confidence: 99%